Kenya Economic Update, March 2016 : Kazi ni kazi - Informal Should Not Be Normal - World Bank Group (World Bank, Nairobi, Kenya, 2016)
This update comes in the wake of three game changing and mutually reinforcing trends. First, monetary policy in the United States (U.S.) will determine the direction of capital flows and currency stability. Second, the persistent decline in commodity prices will determine winners and losers and third, the cooling and rebalancing of the Chinese economy is likely to see a recalibration and change in the direction of trade. Kenya’s growth will depend on the net impact of these global trends on the one hand and the domestic policy response on the other. Growth in 2015 is estimated at 5.6 percent, and is projected to rise to 5.9 percent in 2016 and 6 percent in 2017. The economy has created more jobs in the recent years, but these are low productivity mainly in the informal services sector and are not associated with higher value added. In the next ten years, nine million youth will enter the labor market, a majority will continue to find jobs in the informal sector. To improve productivity of these jobs, policy interventions can be geared towards increasing access to broad skills beyond formal education, creating linkages between formal and informal firms, and helping small scale firms enter local and global value chains. To encourage private sector growth and create better jobs, the business environment must improve. Finally, Kenya can leverage the changes in the global economy to recalibrate its trade as a platform for structural change and provide the impetus for higher levels of growth and creation of productive jobs.